Biomass-derived biochar for CO2 adsorption: Physicochemical design, adsorption kinetics, isotherm modeling, and carbon-management perspectives - Baala H. Anandapadmanaban; Shu-Hui Liu; Chi-Wen Lin; Tzung-Han Chou; Rabia Tasaduq Hussain (Biomass and Bioenergy, 2027)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Melatonin attenuates gentamicin-induced cochlear hair cell injury by modulating the cGAS–STING signaling pathway - Han-gui Lu; Shuang-le Wang; Guo-feng Wen; Chuang-wei Li; Xin-sheng Lin (Tissue and Cell, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Dielectrically tuned core-shell microwave-responsive sorbents for high-efficiency direct air capture - Wenjing Li; Mingxing Zhou; Xiaoyan Ji; Yunxia Wen; Han Lin; Xiaohua Lu; Xinwei Zhang; Xiwen Zhang; Tuo Ji; Shuandi Hou; Jiahua Zhu (Chemical Engineering Journal, 2026)

Individual and combined exposures to polystyrene nanoplastics and benzophenone-3 induce developmental, behavioral and transcriptomic impairments in marine larval clownfish (Amphiprion frenatus) - Yankun Zhang; Fang Lin; Shaobai Wen; Muhammad Junaid; Han Qian; Xiaoping Diao (Marine Pollution Bulletin, 2026)

Process-oriented design of 3D-printed Fe–Co/biochar cathodes for mass-transfer-enhanced bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Shih-Hao Liu; Chung-Yen Yeh; Tzung-Han Chou; Shu-Hui Liu (Journal of Water Process Engineering, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Preparation of plant-based meat analogues by soft matter method: Effects of NaCl concentrations and addition order - Jing-Wen Zhang; Qin Yang; Hui-Lin Li; Qing-Xuan Liu; Han-Qing Chen (Food Hydrocolloids, 2026)

Residual dissipation, processing factor and risk assessment of three pesticides in peaches from field to juice processing - Zehui Liu; Yujiao Wang; Dianying Men; Lin Ma; Guangyue Wen; Shaoxiang Fei; Hongxia Tang; Yanna Han; Maofeng Dong; Li Zhao (Food Control, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Uncovering strain-induced mechanistic divergence of the oxygen evolution reaction on RuO2 - Guokang Han; Yuqi Yan; Dongyue Xin; Zhe Li; Xiaodan Wen; Jiannan Du; Lin Geng; Chunyu Du (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Forchlorfenuron (CPPU) suppresses fruitlet abscission in Areca catechu by modulating carbohydrate allocation, hormonal dynamics, and lignin biosynthesis - Lin-Kai Wang; Wen-Cheng Fan; Han Gong; Dong-Xia Li; Li-Yun Liu; Meng Li; Jia Li (Planta, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Artificial intelligence-enabled machine olfaction for volatile profiling and food quality decision-making - Yitian Gao; Jun-Hu Cheng; Han Wang; Yuandong Lin; Jinhua Wang; Da-Wen Sun (Food Chemistry, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

An adaptor protein CRK mediates antiviral immunity against white spot syndrome virus via JAK/STAT signaling pathway in Cherax quadricarinatus - Zi-Han Fan; Ling-Ke Liu; Wen-Lin Wu; Hai-Peng Liu (Fish & Shellfish Immunology, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Multidimensional chemoprofiling of hybrid and wild Broussonetia papyrifera : sustainable utilization analysis of wild resource substitutes - Yue Ren; Ziye Cheng; Chunmei Yang; Long Han; Xianjun He; Yuqi Liu; Lin Ma; Chuhan Wang; Ziyi Shan; Wen Qin; Xiaofan Yuan (Natural Product Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Curvature and Slope Control on Turbidity Currents and Sedimentation in Submarine Channels: A Numerical Study - Xinhao Wen; Yuechuan Han; Rui Zhu; Enxian Liu; Xiyan Lin; Yuchen Zhang; Yi Zhao; Yuhui Zhang; Jiajun Feng; Dongmei Tian (Journal of Marine Science and Engineering, 2026)
Submarine channels are critical conduits for sediment transport by turbidity currents, yet the quantitative influence of channel geometry on flow dynamics and sediment segregation remains poorly understood. Based on computational fluid dynamics, we constructed six three-dimensional numerical models of submarine channels with varying curvatures (R1–R3) and axial slopes (R4–R6) using ANSYS Fluent 17.2, with model settings informed by seafloor morphology from the South China Sea. The Eulerian–Eulerian multiphase model coupled with the standard k-ε turbulence model was used to simulate density fields, velocity structures, and sediment distributions. Results show that low-curvature channels exhibit symmetric density evolution and uniform sediment distribution, whereas high curvature induces pronounced asymmetry with a steep outer-bank density front and triggers secondary flow reversal. Increasing curvature also enhances flow thickness and radial mass flux. Increasing axial slope markedly elevates downstream velocity (0.09 to 0.16 m/s), reduces flow thickness, and shifts sediment distribution toward the inner bank without inducing secondary flow reversal. This study provides a parametric comparison of curvature versus slope effects on turbidity current dynamics and sedimentation patterns under fixed-bed, rectangular-channel assumptions. The findings offer a qualitative reference for interpreting sedimentary architectures in deep-water systems such as those in the South China Sea and analogous rift basins. Results are hypothesis-generating, pending further validation with field data and morphodynamic modeling.

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Biodegradable mulch film-enriched with biochar, chicken feather, and oyster shell powder for improved soil quality and crop productivity - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Environmental Research, 2026)

Nb5+ pre-intercalation synergistically regulates layered vanadates for high-performance aqueous Zn-ion batteries - Shenglin Zhong; Denglian Chen; Xiang Hu; Han Lin; Menghui Mu; Zhenhai Wen; Jiangcong Zhou (Chemical Engineering Journal, 2026)

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

Bioaccumulation of rare earth elements (REEs) and trace metals in corals of the South China Sea - Yao-Wen Qiu; Han-Lin Qiu (Marine Chemistry, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

Rapid enrichment of ternary carbon-fixing microbial consortia from anaerobic sludge via pressurized pre-autotrophic strategy for scalable microbial electrosynthesis - Lin-xiao Li; Tian-tian Yang; Yue Yuan; Yi-lian Han; Qian Zhao; Wen-han Wang; Yue Sun; Xiao-xin Cao; Xin-lei Jiang; Tian Li; Xin Wang (Bioresource Technology, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

In-situ construction of novel dual bismuth–rich Bi4O5Br2/Bi7O9I3 S-scheme heterojunction with enhanced photocatalytic activity for degradation of diverse persistent organic pollutants - Jia-Lin Zong; Hui-Long Wang; Hao Huang; Yi-Hui Zhao; Li-Juan Han; Wen-Feng Jiang (Journal of Environmental Chemical Engineering, 2026)

Comprehensive characterization of transcriptional regulation during HCG-induced follicle maturation in mandarin fish (Siniperca chuatsi): Insights from transcriptomics - Mingqing Zhang; Zixuan E; Han Wen; Yingshi Tang; Shujia Liao; Lin Tang; Fengying Yan; Yong Zhang; Shuisheng Li (Animal Reproduction Science, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Design of asymmetric combined flow-guiding valve core structure in hydraulic spool valve - Zhao-tong Wang; Wen-qing Li; Xu-han Wang; Tong An; Zhen-hao Lin; Zhi-jiang Jin; Jin-yuan Qian (Annals of Nuclear Energy, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Efficient bridge pier scour profile prediction by an enhanced Bayesian DeepONet - Zhao Chen; Han Lin; Dingzhu Zhashi; Wen Xiong; C.S. Cai (Ocean Engineering, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Photothermal-pancaking synergy in interfacial absorption enables rapid purification of viscous oil-in-water emulsions - Ruoxuan Li; Chaofan Zhu; Ching-Wen Lou; Kaifang Xie; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Chemical Engineering Journal, 2026)

Continuous positive airway pressure on left ventricular ejection fraction in obstructive sleep apnea and heart failure with reduced ejection fraction: a systematic review and meta-analysis - Chou-Han Lin; Yen-Wen Wu; Chih-Chieh Yu (Sleep and Biological Rhythms, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Host acetyl-CoA pathways support WSSV replication - Shu-Wen Cheng; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Rice straw–derived biochar-enriched biodegradable mulch film for enhancing soil organic carbon - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Bioresource Technology Reports, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Atmospheric nitrogen deposition to cropland in Fujian province, China - Ziyin Yu; Mengjuan Han; Zhang Wen; Wenqing Li; Changzheng Wu; Xin Ma; Wen Xu; Ruotong Si; Xiaoping Xia; Aohan Tang; Lin Zhang; Goulding Keith; et al. (Atmospheric Environment, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

A novel hydrogel electrolyte for self-powered sensing and safe energy storage systems in extreme environments - Wen Jiang; Yang Tao; Qiuxiang Yang; Yudong Wang; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Yu Han; Xia Cao (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Isolation and characterization of Pseudomonas sp. QX11 with high-efficiency aerobic denitrification for eutrophication control in aquaculture - Shanrui Shen; Yiyi Zhou; Hongli Cheng; Han Qian; Jun Wen; Chunmei Lin; Xiaofang Lai (Science of The Total Environment, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Heteroatom- and bonded tailored Schottky barrier in Ti₃C₂ MXene/carbon nitride heterojunctions toward efficient photocatalysis - Weinan Xing; Huage Lin; Weifan Shao; Ning Jian; Teng Liu; Shanpeng Wen; Jiangang Han; Guangyu Wu (Chemical Engineering Journal, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

LINE-1 DNA methylation mediates smoking-related risk in site-specific urothelial carcinoma: a Taiwan case–control study - Chien-Hung Lin; Peir-Haur Hung; Chao-Hsiang Chang; Han Chang; Mu-Chi Chung; Wen-Chi Chang; Chi-Jung Chung (Archives of Toxicology, 2025)

Upcycling electroplating sludge into nanoflower-structured Cu-MOFs for efficient Fenton-like degradation of organic dyes - Jia-Yin Lin; Si-Han Yu; Jun-Ren Shih; Tsai-Hsuan Hsieh; Chih-Ying Wang; Jen-Yu Huang; Nai-Wen Tsao (Journal of Water Process Engineering, 2025)

Honey-processed Astragalus polysaccharides exhibit enhanced Qi-tonifying effects via structural modifications and microbiome-metabolome regulation - Zhaohui Lin; Lili Lu; Wenlong Guo; Shuyu Han; Yufei Tian; Hongyuan Chen; Wen Rui (Food Bioscience, 2025)

Optimization of in-situ synthesis of methane in microbial electrochemical systems: influence of substrate concentration, polymerization degree, and applied voltage - Cuixia Liu; Wen Liu; Shengao Meng; Dongyu Han; Zhihao Pan; Junhua Chen; Chunmian Lin (Chemical Engineering Journal, 2025)

Effects of bulk-rock chemistry on paragonite stability in high-pressure epidote-amphibolites from the Yuli metamorphic belt, Taiwan - Wen-Han Lo; Chin-Ho Tsai; Ioannis Baziotis; Sun-Lin Chung; Chiao Liu; Yoshiyuki Iizuka; Hao-Yang Lee (Contributions to Mineralogy and Petrology, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Identification of a novel strain of carp edema virus affecting Songpu mirror carp in Liaoning, China - Wen Shi; Bing Han; Huilin He; Ruixue Feng; Siyi Guo; Xuanyu Ren; Jinshan Huang; Xu Lin; Jiyuan Yin; Xiaonan Lv; Min Liu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

T-2 toxin induces cardiac fibrosis by causing metabolic disorders and up-regulating Sirt3/FoxO3α/MnSOD signaling pathway-mediated oxidative stress - Lichun Qiao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jingming Zhan; Feidan Deng; Miaoye Bao; Huifang He; Xinyue Wen; Huan Deng; Xining Wang; Yujie He; et al. (Journal of Environmental Sciences, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Half-day (daytime and nighttime) precipitation extremes in China: Changes and attribution from 1981 to 2022 - Jiahao Han; Shibo Fang; Xiaomao Lin; Zhanhao Zhang; Man Li; Yanru Yu; Wen Zhuo; Xinyu Wang (Global and Planetary Change, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Experimental investigation on the soil arching effect induced by deep-buried shield tunneling - Ren-Peng Chen; Xu Song; Fan-Yan Meng; Han-Lin Wang; Yang Liu; Lei Wen (Tunnelling and Underground Space Technology, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Triboelectric materials with UV protection, anti-bacterial activity, and green closed-loop recycling for medical monitoring - Jiandan Liang; Qiuxiang Yang; Ce Zhang; Wen Jiang; Shounian Cheng; Yang Tao; Lin Peng; Yu Han; Xia Cao; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

A high selective separation method for high-purity polysaccharides from dandelions by density-oriented deep eutectic solvent ultrasonic-assisted system - Han Zhang; Yu Lin; Yanan Bao; Wen-Jing Li; Bo Hong; Min Zhao (Sustainable Chemistry and Pharmacy, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Integration of multiple observations for validation of mechanisms of earthquake-triggered groundwater level Anomalies: 2016 Taiwan Meinong earthquake - Shih-Jung Wang; Yan-Yao Lin; Ying-Han Chen; Chia-Lin Chung; Wen-Chi Lai; Chien-Chung Ke (Journal of Hydrology, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Optimizing tomato waste hydrolysate for enhanced fucoxanthin biosynthesis in mixotrophic cultivation of Isochrysis galbana - Xi-Wen Fan; Han Sun; Derek M. Ayittey; Zhi-gang Zhou; Carol Sze Ki Lin; Tao Tang; Zheng Sun (Bioresource Technology, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Rapid and accurate detection of total nitrogen in the different types for soil using laser-induced breakdown spectroscopy combined with transfer learning - Peng Lin; Changbo Song; Chongshan Yang; Mengjie Zhang; Shixiang Ma; Jiangtao Wen; Daming Dong; Yuxing Han (Computers and Electronics in Agriculture, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

A novel BiVO4/vermiculite Z-scheme heterojunction with enhanced removal rate of dyes through adsorption photodegradation synergistic mechanism - Lin Han; Liying Wen; Xiaoju Yue; Jinnong Wang; Yue Liu; Yuanhao Wang; Shifeng Wang (Journal of Water Process Engineering, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

Networking SiO2-Al2O3 and amines into robust and long-lasting molded sorbents for continuous CO2 capture - Tong Zhou; Zhinan Wu; Yunxia Wen; Zhengxing Dai; Shuailong Song; Han Lin; Xin Feng; Xiaohua Lu; Tuo Ji; Jiahua Zhu (Chemical Engineering Journal, 2024)

Exploring the effects of pemetrexed on drug resistance mechanisms in human lung adenocarcinoma and its association with PGRMC1 - Ssu-Yun Wu; En-Chi Liao; Yueh-Feng Wen; Yi-Shiuan Wang; Han Meng; Hsiu-Chuan Chou; Hong-Lin Chan (Chemico-Biological Interactions, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Corrigendum to “An efficient approach for identifying important biomarkers for biomedical diagnosis” [Biosystems 237 (2024) 105163] - Jing-Wen Huang; Yan-Hong Chen; Frederick Kin Hing Phoa; Yan-Han Lin; Shau-Ping Lin (BioSystems, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Global quantitative synthesis on the patterns and drivers of funneling ratio and enrichment ratio for stemflow - Meng-Di Wu; Zhi-Yun Jiang; Xiao Yang; Buerlan Yeerbolati; Lin Huang; Ying-Yin Zhong; Han-Wen Zhang; Xiao-Yan Li (CATENA, 2024)

Association Between COVID-19 and Neurological Diseases: Evidence from Large-Scale Mendelian Randomization Analysis and Single-Cell RNA Sequencing Analysis - Lin Huang; Yongheng Wang; Yijie He; Dongyu Huang; Tong Wen; Zhijie Han (Molecular Neurobiology, 2024)
Observational studies have suggested that SARS-CoV-2 infection increases the risk of neurological diseases, but it remains unclear whether the association is causal. The present study aims to evaluate the causal relationships between SARS-CoV-2 infections and neurological diseases and analyzes the potential routes of SARS-CoV-2 entry at the cellular level. We performed Mendelian randomization (MR) analysis with CAUSE method to investigate causal relationship of SARS-CoV-2 infections with neurological diseases. Then, we conducted single-cell RNA sequencing (scRNA-seq) analysis to obtain evidence of potential neuroinvasion routes by measuring SARS-CoV-2 receptor expression in specific cell subtypes. Fast gene set enrichment analysis (fGSEA) was further performed to assess the pathogenesis of related diseases. The results showed that the COVID-19 is causally associated with manic (delta_elpd, − 0.1300, Z -score: − 2.4; P = 0.0082) and epilepsy (delta_elpd: − 2.20, Z -score: − 1.80; P = 0.038). However, no significant effects were observed for COVID-19 on other traits. Moreover, there are 23 cell subtypes identified through the scRNA-seq transcriptomics data of epilepsy, and SARS-CoV-2 receptor TTYH2 was found to be specifically expressed in oligodendrocyte and astrocyte cell subtypes. Furthermore, fGSEA analysis showed that the cell subtypes with receptor-specific expression was related to methylation of lysine 27 on histone H3 (H3K27ME3), neuronal system, aging brain, neurogenesis, and neuron projection. In summary, this study shows causal links between SARS-CoV-2 infections and neurological disorders such as epilepsy and manic, supported by MR and scRNA-seq analysis. These results should be considered in further studies and public health measures on COVID-19 and neurological diseases.

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Evaluating the effect of Multi-Scale droughts on autumn phenology of global land biomes with satellite observation - Ronglei Zhou; Yangyang Liu; Xueqing Wang; Xu Chen; Gaohui Duan; Peidong Han; Ziqi Lin; Haijing Shi; Zhongming Wen (Journal of Hydrology, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

Straw returning and nitrogen reduction: Strategies for sustainable maize production in the dryland - Miaomiao Zhang; Ning Yang; Shiguang Wang; Xiaoqing Han; Pengfei Dang; Guoqing Li; Shuyue Wen; Lin Zhang; Jiquan Xue; Xiaoliang Qin; Kadambot H.M. Siddique (Journal of Environmental Management, 2024)

Online monitoring lignocellulosic particles by focus beam reflectance measurement for efficient bioprocessing - Ji-Wen Yao; Xiao-Yan Huang; Yen-Han Lin; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Co-occurrence of elevated arsenic and fluoride concentrations in Wuliangsu Lake: Implications for the genesis of poor-quality groundwater in the (paleo-)Huanghe (Yellow River) catchment, China - Ya-Ni Yan; Jun-Wen Zhang; Na Wu; Zi-Han Xia; Lin Liu; Zhi-Qi Zhao (Water Research, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Prediction and correlation study of dioxin emissions classifications from municipal solid waste incinerators - Wenhua Yin; Chaojun Wen; Lijun Liu; Danping Xie; Jinglei Han; Xiaoqing Lin (Atmospheric Pollution Research, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Simultaneous determination of seawater trimethylamine and methanol by purge and trap gas chromatography using dual nitrogen-phosphorus detector and flame-ionization detector - Fei Jiang; Zhen Zhou; Jin-Yan Wang; Wen-Jia Guan; Lei-Gang Han; Xian-Biao Lin; Guang-Chao Zhuang (Frontiers in Marine Science, 2024)
Compounds containing one carbon atom or no carbon-carbon bond (C1 compounds), such as trimethylamine and methanol, are important climate relevant gases in the atmosphere and play key roles in global warming. The ocean is a significant source or sink of such compounds, while the concentrations of trimethylamine and methanol in seawater remain largely unconstrained due to the analytical challenges involved. Therefore, it is necessary to establish a continuous, rapid and sensitive method for the determination of these compounds with high polarity, volatility or solubility at low seawater concentrations. Here we developed a purge and trap system, coupled to a gas chromatography equipped with dual nitrogen phosphorus detector (NPD) and flame ionization detector (FID) for the simultaneous online analysis of trimethylamine and methanol at nanomolar range using a small sample volume (~ 10 mL). The dual detection of trimethylamine and methanol with NPD or FID was achieved by installing a capillary flow splitter between the capillary column and detectors. After modification and optimization of the setup and conditions, excellent linearity (R 2 > 0.99) and repeatability (< 6%) were obtained for both compounds; the detection limits for trimethylamine and methanol were 0.3 nM and 17.6 nM, respectively. Using this method, water samples collected from coastal and open ocean were analyzed; trimethylamine and methanol concentrations ranged from 0.6 to 18.8 nM and 26.0 to 256.2 nM, respectively. Collectively, this method allowed for online, rapid, sensitive and simultaneous quantification of trace trimethylamine and methanol concentrations with low-cost instrumentation and small sample volume, which makes it promising for further application in volatile compounds analysis in marine environments.

Behavioral Lifestyle Intervention Program Using Mobile Application Improves Diet Quality in Adults With Prediabetes (D’LITE Study): A Randomized Controlled Trial - Chad Yixian Han; Su Lin Lim; Kai Wen Ong; Jolyn Johal; Aarti Gulyani (Journal of the Academy of Nutrition and Dietetics, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

An efficient approach for identifying important biomarkers for biomedical diagnosis - Jing-Wen Huang; Yan-Hong Chen; Frederick Kin Hing Phoa; Yan-Han Lin; Shau-Ping Lin (BioSystems, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

A digital platform for One-Pot signal enhanced foodborne pathogen detection based on mesophilic argonaute-driven polydisperse microdroplet reactors and machine learning - Junping Wen; Minjie Han; Niu Feng; Guoxun Chen; Feng Jiang; Jianhan Lin; Yiping Chen (Chemical Engineering Journal, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Discriminating the impacts of vegetation greening and climate change on the changes in evapotranspiration and transpiration fraction over the Yellow River Basin - Yangyang Liu; Ziqi Lin; Zijun Wang; Xu Chen; Peidong Han; Bo Wang; Zhenqian Wang; Zhongming Wen; Haijing Shi; Zhixin Zhang; Wei Zhang (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Effect of hydraulic regime on sulfur-packed bed performance: Denitrification and disproportionation - Yi-Lu Sun; Wei Wei; Huu Hao Ngo; Wen Shan Guo; Xue-Ning Zhang; Bing-Jie Ni; Wei-Qin Zhuang; Han-Lin Wang (Environmental Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

A resilience assessment framework for existing underground structures under adjacent construction disturbance - Kaihang Han; Dongmei Zhang; Xiangsheng Chen; Dong Su; Jiann-Wen Woody Ju; Xing-Tao Lin; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Oxygen-producing composite dressing activated by photothermal and piezoelectric effects for accelerated healing of infected wounds - Yen-Han Lai; Snigdha Roy Barman; Anindita Ganguly; Arnab Pal; Jui-Han Yu; Syun-Hong Chou; E-Wen Huang; Zong-Hong Lin; San-Yuan Chen (Chemical Engineering Journal, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

MaizeNetome: A multi-omics network database for functional genomics in maize - Jia-Wu Feng; Linqian Han; Hao Liu; Wen-Zhao Xie; Hanmingzi Liu; Lin Li; Ling-Ling Chen (Molecular Plant, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Cabernet sauvignon dry red wine ameliorates atherosclerosis in mice by regulating inflammation and endothelial function, activating AMPK phosphorylation, and modulating gut microbiota - Xinlong Cheng; Xue Han; Liangfu Zhou; Yasai Sun; Qian Zhou; Xuan Lin; Zhe Gao; Jie Wang; Wen Zhao (Food Research International, 2023)

Correction: PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Coating zero valent iron onto hollow carbon spheres as efficient electrocatalyst for N2 fixation and neutral Zn-N2 battery - Huici Qiao; Yu Han; Lin Yao; Xin Xu; Jun Ma; Bin Wen; Jie Hu; Hao Huang (Chemical Engineering Journal, 2023)

A quantitative approach for sealing capacity evaluation of caprock in candidate of aquifer gas storage - Shanpo Jia; Meng Xu; Caoxuan Wen; Borui Li; Tuanhui Liu; Zengqiang Xi; Lin Han (Environmental Science and Pollution Research, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Characterization of procyanidin extracts from hawthorn (Crataegus pinnatifida) in human colorectal adenocarcinoma cell line Caco-2, simulated Digestion, and fermentation identified unique and novel prebiotic properties - Xue Han; Qian Zhou; Zhe Gao; Guanying Bianca Xu; Hong Chen; Bimal Chitrakar; Yasai Sun; Wen Zhao; Xuan Lin; Kaixuan Zhou; Zhisheng Zhang (Food Research International, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Soil microbial community is resilient to thinning disturbance - Wan-Rou Lin; Wen-Cheng Chen; Pi-Han Wang (Tropical Ecology, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Photothermal and Concus Finn capillary assisted superhydrophobic fibrous network enabling instant viscous oil transport for crude oil cleanup - Ting Dong; Yanhui Liu; Na Tian; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

VUV/UV oxidation performance for the elimination of recalcitrant aldehydes in water and its variation along the light-path - Wan-Yue Ouyang; Wen-Long Wang; Yi-Lin Zhang; Han-Ying Cai; Qian-Yuan Wu (Water Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

N-type small molecule electron transport materials with D-A-D conjugated core for non-fullerene organic solar cells - Dan Zhou; Yubing Li; Hehui Zhang; Haolan Zheng; Xingxing Shen; Wen You; Lin Hu; Liangjing Han; Yongfen Tong; Lie Chen (Chemical Engineering Journal, 2023)

Osteomodulin protects dental pulp stem cells from cisplatin-induced apoptosis in vitro - Ting Dong; Wen-zhen Lin; Xiao-han Zhu; Ke-yong Yuan; Li-li Hou; Zheng-wei Huang (Stem Cell Reviews and Reports, 2023)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2022)
Acute kidney injury (AKI) is a common severe acute syndrome caused by multiple factors and is characterized by a rapid decline in renal function during a short period. Bone marrow mesenchymal stromal cells (BMSCs) are effective in treating AKI. However, the mechanism of their beneficial effects remains unclear. PTEN-induced kinase 1 (PINK1) may play an important role in kidney tissue repair. In this study, we explored the effect of PINK1 overexpression on enhancing BMSC-mediated repair of AKI. In this study, ischaemia/reperfusion-induced AKI (IRI-AKI) in mice and a hypoxia-reoxygenation model in cells were established, and the indices were examined by pathology and immunology experiments. After ischaemia/reperfusion, PINK1 overexpression reduced apoptosis in injured kidney tissue cell, decreased T lymphocyte infiltration, increased macrophage infiltration, and alleviated the inflammatory response. PINK1 relieved the stress response of BMSCs and renal tubular epithelial cells (RTECs), reduced apoptosis, altered the release of inflammatory factors, and reduced the proliferation of peripheral blood mononuclear cells (PBMCs). In conclusion, BMSCs and RTECs undergo stress responses in response to hypoxia, inflammation and other conditions, and overexpressing PINK1 in BMSCs could enhance their ability to resist these stress reactions. Furthermore, PINK1 overexpression can regulate the distribution of immune cells and improve the inflammatory response. The regulation of mitochondrial autophagy during IRI-AKI maintains mitochondrial homeostasis and protects renal function. The results of this study provide new strategies and experimental evidence for BMSC-mediated repair of IRI-AKI.

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Correction to: Higher sequestration of wheat versus maize crop carbon in soil under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Probabilistic stability analysis of embankment slopes considering the spatial variability of soil properties and seismic randomness - Wen-gang Zhang; Jia-hao Wu; Xin Gu; Liang Han; Lin Wang (Journal of Mountain Science, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Higher sequestration of wheat versus maize crop carbon in soils under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Seasonal variation of flavonoid metabolites in leaves of Liquidambar formosana ‘Nanlinhong’ trees revealed by UPLC-ESI–MS/MS - Jiu-Xin Lai; Fu-Rong Lin; Ping Huang; Wen-Ying Guo; Lie-Bao Han; Yong-Qi Zheng (Brazilian Journal of Botany, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

Recycle of synthetic calcium fluoride and waste sulfuric acid to produce electronic grade hydrofluoric acid - Min-Fa Lin; Jhong-Lin Wu; Ken-Lin Chang; Wen-Jhy Lee; Chih-Ping Chang; Yung-Chang Lin; Po-Han Chen (Environmental Science and Pollution Research, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Complete mitochondrial genome of the freshwater fish Acrossocheilus longipinnis (Teleostei: Cyprinidae): genome characterization and phylogenetic analysis - Xiao-Jing Hou; Hung-Du Lin; Wen-Qiao Tang; Dong Liu; Chiao-Chuan Han; Jin-Quan Yang (Biologia, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

DNA methylation of JAK3/STAT5/PPARγ regulated the changes of lipid levels induced by di (2-ethylhexyl) phthalate and high-fat diet in adolescent rats - Qi Xu; Wen Qi; Yuezhu Zhang; Qi Wang; Shuang Ding; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Description of Gemmobacter aestuarii sp. nov., isolated from estuarine surface water and reclassification of Cereibacter changlensis as Gemmobacter changlensis Chen et al. 2013 - Asif Hameed; Mariyam Shahina; Shih-Yao Lin; Wen-Ming Chen; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Archives of Microbiology, 2020)

Numerical Simulation of Large Wave Heights from Super Typhoon Nepartak (2016) in the Eastern Waters of Taiwan - Shih-Chun Hsiao; Hongey Chen; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Wen-Dar Guo; Yung-Ming Chen; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
Super Typhoon Nepartak (2016) was used for this case study because it is the most intense typhoon that made landfall in Taiwan in the past decade. Winds extracted from the Climate Forecast System version 2 (CFSV2) and ERA5 datasets and merged with a parametric typhoon model using two hybrid techniques served as the meteorological conditions for driving a coupled wave-circulation model. The computed significant wave heights were compared with the observations recorded at three wave buoys in the eastern waters of Taiwan. Model performance in terms of significant wave height was also investigated by employing the CFSV2 winds under varying spatial and temporal resolutions. The results of the numerical experiments reveal that the simulated storm wave heights tended to decrease significantly due to the lower spatial resolution of the hourly winds from the CFSV2 dataset; however, the variations in the storm wave height simulations were less sensitive to the temporal resolution of the wind field. Introducing the combination of the CFSV2 and the parametric typhoon winds greatly improved the storm wave simulations, and similar phenomena can be found in the exploitation of the ERA5 dataset blended into the parametric wind field. The overall performance of the hybrid winds derived from ERA5 was better than that from the CFSV2, especially in the outer region of Super Typhoon Nepartak (2016).

Impacts of irrigation methods on greenhouse gas emissions/absorptions from vegetable soils - Xuhong Ye; Hongdou Liu; Xichao Zhang; Jianhui Ma; Bing Han; Wen Li; Hongtao Zou; Yulong Zhang; Xiangui Lin (Journal of Soils and Sediments, 2020)

The Alterations of Copper and Zinc Homeostasis in Acute Appendicitis and the Clinical Significance - Wenhao Lin; Wei Han; Ke Wen; Sunhua Huang; Yao Tang; Zhexuan Lin; Ming Han (Biological Trace Element Research, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Bioaccumulation and Cycling of Polycyclic Aromatic Hydrocarbons (PAHs) in Typical Mangrove Wetlands of Hainan Island, South China - Yao-Wen Qiu; Han-Lin Qiu; Jun Li; Gan Zhang (Archives of Environmental Contamination and Toxicology, 2018)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

MDM2 Degrades Deacetylated Nucleolin Through Ubiquitination to Promote Glioma Stem-Like Cell Enrichment for Chemotherapeutic Resistance - Chiung-Yuan Ko; Chao-Han Lin; Jian-Ying Chuang; Wen-Chang Chang; Tsung-I Hsu (Molecular Neurobiology, 2018)

The different influence of the residual layer on the development of the summer convective boundary layer in two deserts in northwest China - Zhao Lin; Han Bo; Lv Shihua; Wen Lijuan; Meng Xianhong; Li Zhaoguo (Theoretical and Applied Climatology, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

The effects of different irrigation regimes on nitrous oxide emissions and influencing factors in greenhouse tomato fields - Bing Han; Xuhong Ye; Wen Li; Xichao Zhang; Yulong Zhang; Xiangui Lin; Hongtao Zou (Journal of Soils and Sediments, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Protective effects of paeonol on inflammatory response in IL-1β-induced human fibroblast-like synoviocytes and rheumatoid arthritis progression via modulating NF-κB pathway - Ke-feng Zhai; Hong Duan; Lin Luo; Wen-gen Cao; Fang-kai Han; Ling-ling Shan; Xue-mei Fang (Inflammopharmacology, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Hydrology Drives Vegetation Succession in a Tidal Freshwater Wetland of Subtropical Taiwan - Hsing-Juh Lin; Chun-Han Huang; Gwo-Wen Hwang; Chorng-Bin Hsu; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Effects of elevated carbon dioxide concentration on nitrous oxide emissions and nitrogen dynamics in a winter-wheat cropping system in northern China - Yingchun Li; Erda Lin; Xue Han; Zhengping Peng; Wen Wang; Xingyu Hao; Hui Ju (Mitigation and Adaptation Strategies for Global Change, 2015)

Halorientalis brevis sp. nov., Isolated from an Inland Salt Lake of China - Pan-Pan Yuan; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Current Microbiology, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Halosimplex litoreum sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Jia-Qi Xu; Wen-Mei Xu; Zhao Wang; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Halorussus ruber sp. nov., isolated from an inland salt lake of China - Wei-Dong Xu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Kun Yang (Archives of Microbiology, 2015)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

FP-receptor gene silencing ameliorates myocardial fibrosis and protects from diabetic cardiomyopathy - Wen-yuan Ding; Lin Liu; Zhi-hao Wang; Meng-xiong Tang; Yun Ti; Lu Han; Lei Zhang; Yun Zhang; Ming Zhong; Wei Zhang (Journal of Molecular Medicine, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Organic matters and lipid biomarkers in surface sediments from the northern South China Sea: Origins and transport - Weihai Xu; Wen Yan; Zhong Chen; Han Chen; Weixia Huang; Tian Lin (Journal of Earth Science, 2014)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Investigation of array-derived rotation in TAIPEI 101 - Chin-Jen Lin; Wen-Gee Huang; Han-Pang Huang; Bor-Shouh Huang; Chin-Shang Ku; Chun-Chi Liu (Journal of Seismology, 2012)

TFF3 mediated induction of VEGF via hypoxia in human gastric cancer SGC-7901 cells - Bayasi Guleng; Jia Han; Jin-Qiu Yang; Qing-Wen Huang; Jian-Kun Huang; Xiao-Ning Yang; Jing-Jing Liu; Jian-Lin Ren (Molecular Biology Reports, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

ASIP genetic variants and the number of non-melanoma skin cancers - Wen Lin; Abrar A. Qureshi; Peter Kraft; Hongmei Nan; Qun Guo; Frank B. Hu; Majken K. Jensen; Jiali Han (Cancer Causes & Control, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Pharmacokinetics and Pharmacodynamics of Broccoli Sprouts on the Suppression of Prostate Cancer in Transgenic Adenocarcinoma of Mouse Prostate (TRAMP) Mice: Implication of Induction of Nrf2, HO-1 and Apoptosis and the Suppression of Akt-dependent Kinase Pathway - Young-Sam Keum; Tin Oo Khor; Wen Lin; Guoxiang Shen; Ki Han Kwon; Avantika Barve; Wenge Li; Ah-Ng Kong (Pharmaceutical Research, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Effects of C-terminal amino acids truncation on enzyme properties of Aeromonas caviae D1 chitinase - Fu-Pang Lin; Hsu-Han Chuang; Yi-Hsuan Liu; Chia-Yu Hsieh; Pei-Wen Lin; Hsu-Yang Lin (Archives of Microbiology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

A Novel Alginate Lyase with High Activity on Acetylated Alginate of Pseudomonas aeruginosa FRD1 from Pseudomonas sp. QD03 - Lin Xiao; Feng Han; Zhao Yang; Xin-zhi Lu; Wen-gong Yu (World Journal of Microbiology and Biotechnology, 2006)

Effects of Cycle Time on Properties of Aerobic Granules in Sequencing Batch Airlift Reactors - Fang Wang; Feng-lin Yang; Xing-wen Zhang; Yi-hui Liu; Han-min Zhang; Jun Zhou (World Journal of Microbiology and Biotechnology, 2005)

Effects of Growth Regulators on Direct Flowering of Isolated Ginseng Buds in vitro - Choun-Sea Lin; Chang-Tsern Chen; Han-Wen Hsiao; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

An interspecific somatic hybrid between Actinidia chinensis and Actinidia kolomikta and its chilling tolerance - Zun-an Xiao; Lin-chen Wan; Bi-wen Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Zinc supplementation on serum levels and hepatic conversion of thyroid hormones in obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Wen-Han Lin (Biological Trace Element Research, 1998)

Zinc attenuation of GDP binding to brown adipocytes mitochondria in genetically obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Piin-Sheng Chen; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1997)

Zinc supplementation aggravates body fat accumulation in genetically obese mice and dietary-obese mice - Ming-Der Chen; Pi-Yao Lin; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1996)

Dietary copper supplementation increases the catecholamine levels in genetically obese (ob/ob) mice - Wen-Han Lin; Ming-Der Chen; Chih-Chien Wang; Pi-Yao Lin (Biological Trace Element Research, 1995)

Selected metals status in patients with noninsulin-dependent diabetes mellitus - Ming-Der Chen; Pi-Yao Lin; Chung-Tide Tsou; Jyh-Jain Wang; Wen-Han Lin (Biological Trace Element Research, 1995)